(untitled) (SAARC Journal of Agriculture, 2016)
The cutlets prepared in eight different combinations from minced meat of pangas (Pangasius pangasius) were studied for their nutritional composition, texture profile and acceptability. The effects of processing methods on quality of cutlets were also evaluated. Protein, fat and ash contents of the cutlets prepared in different combinations ranged between 13.37 ± 0.38 to 19.73 ± 0.01 %; 11.05 ± 0.14 to 13.98 ± 0.07 % and 1.81 ± 0.03 to 5.59 ± 0.22 % respectively. More protein and fat contents, less hardness and cutting strength values were observed in cutlets made from cooked mince compared to the cutlets from raw mince. Cutlets from all the lots were sensorially acceptable but there was no significant difference (p>0.05) found between cutlets made from raw and cooked mince with or without potato, batter and bread crumbs. Hence, sensorially acceptable cutlets from pangas catfish mince can be prepared using any of the eight combinations studied based on the requirement or economic viability. SAARC J. Agri., 14(1): 25-36 (2016)